1981
DOI: 10.1099/00221287-127-2-361
|View full text |Cite
|
Sign up to set email alerts
|

The Attachment to, and Invasion of HeLa Cells by Salmonella typhimurium: The Contribution of Mannose-sensitive and Mannoseresistant Haemagglutinating Activities

Abstract: The association of the haemagglutinating activities of Salmonella typhimurium cultures with bacterial adhesion to HeLa cells, and the internalization of the bacteria by HeLa cells, was studied. Adhesion was not inhibited by alpha-methyl-D-mannoside (i.e. adhesion was mannose-resistant), and only four of the six strains tested produced type 1 fimbriae and the associated mannose-sensitive haemagglutinin (MSHA). The other two strains belonged to the non-fimbriate FIRN biogroup. Cultures of all six strains contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
55
0
1

Year Published

1984
1984
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 11 publications
1
55
0
1
Order By: Relevance
“…Strains grown at 16ºC showed decreased mannose-sensitive hemagglutination compared with those grown at 37ºC (Table 1). These results agree with previous reports on the expression of Salmonella hemagglutinins (7,14,24,31).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Strains grown at 16ºC showed decreased mannose-sensitive hemagglutination compared with those grown at 37ºC (Table 1). These results agree with previous reports on the expression of Salmonella hemagglutinins (7,14,24,31).…”
Section: Resultssupporting
confidence: 83%
“…Nonfimbrial soluble hemagglutinins have been described in Salmonella spp. (14,19,26), but they are mannoseresistant and hence different from the mannose-sensitive hemagglutinin identified here.…”
Section: Resultsmentioning
confidence: 94%
“…Many virulence functions are encoded on the salmonella chromosome. These include: adherence to (Jones and Richardson, 1981), invasion into (Galan and Curtiss, 1989), and transcytosis through (Finlay et al, 1988) mammalian epithelial cells, which is believed to simulate infection of the gut; PhoP-regulated resistance to phagocytic defences important in lymphoid tissues (Miller et al, 1990;Fields et al, 1989); and smooth lipopolysaccharide (LPS) necessary for resistance to complement-mediated bacteriolysis in blood (Joiner, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…As for the genetic factors determining the pathogenicity of Salmonella, several investigators reported that serovar-specific large plasmids of Salmonella spp. are involved in systemic Salmonella infections (9,11,13). However, we recently reported that plasmids of S. braenderup and S. typhimurium are not involved in human acute enterocolitis (8).…”
Section: Introductionmentioning
confidence: 99%